Motion planning of hyper redundant manipulators based on a new geometrical method - Yahya, S.; Mohamed, H.A.F.; Moghavvemi, M.; Yang, S.S. (2009)
Motion planning capability is an essential part of an industrial robot system. Therefore research in robot motion planning remains as one of the important fields of study in the task of building industrial robot systems. A new method for the motion planning is presented in this paper. The basic idea is to find a smooth path consisting of points close enough to each other. Then the computation of the inverse kinematics for these points is accomplished with the help of a new proposed geometrical method to solve the problem of multi-solution caused by redundancy. The advantage of this method is that the angles between the adjacent links are the same, it makes controlling these links easier and the movement of the manipulator itself more stable. This method can be used for the equal length links planar manipulators. To demonstrate the effectiveness of this proposed method, experiments were conducted on a 10-links hyper redundant manipulator in this paper.